ANALISIS KOMPARASI PENDAPATAN USAHATANI PADA PROGRAM BENIH MANDIRI PETANI PADI SAWAH DI DESA PUDAK, KECAMATAN KUMPEH ULU KABUPATEN MUARO JAMBI - Fathoni, Zakky; Farida, Aulia (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2019)
Agriculture contributes considerably in supporting development in rural communities. One of them is food agriculture. Food is one of the government's special concerns regarding development policies. There are many agricultural policies related to food in Indonesia. One of them is food sovereignty. The direction of food sovereignty is to strengthen food security towards food independence. To achieve food independence, one of the programs carried out by the government is the Seed Independent Village program. This study aims to determine the farm income of rice farmers from the independent seed village program, to determine the comparison of farmers' farm income from the sale of grain to rice seed sales. The study was conducted in Pudak Village, Kumpeh Ulu District, Muaro Jambi Regency. This research is a quantitative study, where the data obtained are primary and secondary data, obtained through in-depth interviews and questionnaires. Analysis of the data used in this research is descriptive analysis and income analysis. The results obtained indicate that the average level of income of paddy farmers in the paddy and seed farmers group is Rp. 37,768,816.25 / MT, greater than the rice farmers group of Rp. 25,894,292.5 / MT. The results of the average difference test show that there is a significant difference between the level of income of farmers who produce grain and seeds with farmers who only produce grain. With the additional effort to produce seeds in lowland rice farming in Pudak Village, Kumpeh Ulu sub-district has a positive effect in increasing the income of lowland rice farming. Keywords: Mandiri Seed, Rice Field Farming Inco